LEACHATE TREATMENT TECHNOLOGY ALTERNATIVE SELECTION IN THE LANDFILL USING ANALYTIC NETWORK PROCESS (ANP) - Mauluddina, Gina
Leachate produced at the landfill has the potential to cause environmental impacts to social conflicts. This things indicates that the selection of leachate treatment is complex because it is affected by various aspects (criteria) and the relation between criteria. Alternative leachate treatment technologies are listed in Appendix III of Minister of Public Works Regulation No. 03 of 2003 concerning the Implementation of Solid Waste Infrastructure and Facilities in Household Waste Handling and Household Waste. The selection of technology alternatives will be done by multicriteria analysis in the form of Analytic Network Process (ANP). The ANP method can model problems using interrelation between criteria. In ANP study, it is strengthened by analyzing the relation between sub-criteria using Dependence and Driving Power Analysis (DDPA). Results of the analysis is identified by 11 sub-criteria in 5 criteria (economic, environmental, social, technical and institutional). An alternative scenario for leachate treatment consists of 5 combinations of biological and chemical processing. The alternative selection process was obtained through a paired matrix questionnaire of 36 respondents consisting of groups of practitioners, institutions, academics and operators who were then processed using the super decision software. ANP analysis results from all respondents showed that the economic criteria is a major consideration in the selection of leachate treatment alternative (0,3219 weight). Sub criteria affecting decision-making significantly are water protection (L2), regulation availability (K2), and community acceptance (S2). Alternative 1 (Anaerobic, Facultative Pond, Maturasi and Biofilter) is the highest results (0,4893 weight) with preference sintesis the priorities of the alternatives.